2008
DOI: 10.1007/s11605-007-0377-7
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Imaging on the Negative Appendectomy Rate in Pregnancy

Abstract: Appendectomy is the most common non-gynecologic surgery performed during pregnancy. Little data exist on the accuracy of imaging studies in the diagnosis of appendicitis in pregnancy. The objective of this study was to evaluate the probability of ultrasound and computed tomography (CT) scan in diagnosing appendicitis in pregnancy, as reflected in the negative appendectomy rate. We retrospectively reviewed the charts of 86 pregnant women who underwent an appendectomy between January 1, 1997 and January 1, 2006.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
0
12

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 13 publications
5
44
0
12
Order By: Relevance
“…In one study, negative laparotomy rates among patients who underwent (1) clinical examination alone, (2) clinical and ultrasound examination, and (3) clinical assessment, and ultrasound followed by CT were 54 (7/13) 36 (20/55) and 8% (1/13), respectively. 45 …”
Section: 28mentioning
confidence: 99%
See 1 more Smart Citation
“…In one study, negative laparotomy rates among patients who underwent (1) clinical examination alone, (2) clinical and ultrasound examination, and (3) clinical assessment, and ultrasound followed by CT were 54 (7/13) 36 (20/55) and 8% (1/13), respectively. 45 …”
Section: 28mentioning
confidence: 99%
“…There is some evidence suggesting that the higher negative laparotomy rate in pregnant women is associated, at least in part, to a reluctance to perform the pre-operative CT in such patients. 45,49 A seemingly normal appendix must be removed for histological examination, as it may then reveal acute inflammation; excision avoids the potential for further evaluation, and intervention for suspected appendicitis and appendectomy is associated with a very low risk of complications. 35 Cesarean section is rarely indicated at the time of appendectomy.…”
Section: Appendectomymentioning
confidence: 99%
“…They reported a significant reduction in the negative appendectomy rate in the ultrasound/CT group compared to the clinical evaluation group (8% vs. 54%, p<0.05). 16 Appendectomy can be performed through laparoscopy or open technique. During the past decades laparoscopic appendectomy has gained wide acceptance for the treatment of acute appendicitis.…”
Section: Discussionmentioning
confidence: 99%
“…US and magnetic resonance imaging (MRI) are not associated with ionizing radiation, have not been shown to have any deleterious effects on pregnancy, and should be used when feasible. [4,[9][10][11] Retrospective studies have suggested that MRI of the appendix is useful in delineating the presence of appendicitis in pregnant women, but the small number of patients in these studies limits the inference that can be drawn. [12] There are also studies using computed tomography (CT) for the diagnosis of acute appendicitis in pregnancy; however, due to the deleterious effects of ionizing radiation on the fetus, it is suggested to be used only in severe trauma patients with pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…[4,[13][14][15] Wallace et al [10] reported an overall negative appendectomy rate of 37% for pregnant patients with presumed acute appendicitis. They also reported no difference in the negative appendectomy rate with the addition of CT scan after US.…”
Section: Discussionmentioning
confidence: 99%